Incidence and Risk Factors of Surgical Site Infections After Cesarean Section: A Retrospective Analysis - Salma Mumtaz, Asma Mumtaz, Khalid Ali, Monica Punshi, Abdul Ghaffar Arain, Pavan Kumar, Erum Fatima, Asma Nadeem, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Surgical site infection (SSI) is one of the most frequent postoperative complications following cesarean section and remains a major contributor to maternal morbidity, prolonged hospital stays, and increased healthcare costs, especially in low- and middle-income countries. Objective: To determine the incidence and risk factors associated with surgical site infections among women undergoing cesarean section. Methodology: This descriptive cross-sectional study was conducted at Khyber Teaching Hospital Peshawar from June 2022 to June 2023. A total of 365 post-cesarean patients were enrolled using non-probability consecutive sampling. Demographic, obstetric, and clinical data were recorded using a structured proforma. Patients were followed for 30 days postoperatively to assess the occurrence of SSI according to CDC criteria. Results: The mean age of patients was 29.8 ± 5.7 years, and 67.7% of cesarean sections were emergency procedures. The overall incidence of SSI was 12.6% (46 out of 365 patients). Among these, superficial incisional infections were most common (63%), followed by deep (26%) and organ/space infections (11%). Staphylococcus aureus was the predominant pathogen (39.1%), followed by Escherichia coli (26%). Significant predictors of SSI included obesity (p = 0.02), diabetes mellitus (p = 0.01), anemia (p = 0.04), prolonged rupture of membranes (p = 0.03), longer operative duration (p = 0.01), and emergency cesarean section (p = 0.01). Conclusion: It is concluded that surgical site infections remain a considerable postoperative burden after cesarean delivery. Obesity, diabetes, prolonged rupture of membranes, anemia, and emergency surgery were significant contributing factors. Keywords: Cesarean section, surgical site infection, maternal morbidity, risk factors, postoperative